INOVASI KBM MEDIA PERMAINAN ULAR TANGGA BERBASIS ETNOMATEMATIKA UNTUK MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR - Gunardi, Ari; Dzil Ikrom, Fadhli (LPPM Universitas Bina Bangsa, 2024)
The method used is a qualitative research method. A research method that uses numerical data to test hypotheses, measure variables, analyze relationships between variables and answer research questions. In this method, data is collected systematically using standardized measurement instruments and the data is interpreted using statistical analysis. The purpose of quantitative research is to obtain data that can be measured and analyzed objectively and to make generalizations about the relationship between the variables studied. Research requires a method that is tailored to the problem and purpose of the research. In other words, the research method plays an important role in data collection and analysis. The purpose of this study is to describe the use of the